2022
DOI: 10.1093/nsr/nwac174
|View full text |Cite
|
Sign up to set email alerts
|

Hologenomic insights into mammalian adaptations to myrmecophagy

Abstract: Highly specialized myrmecophagy (ant- and termite-eating) has independently evolved multiple times in species of various mammalian orders and represents a textbook example of phenotypic evolutionary convergence. We explored the mechanisms involved in this unique dietary adaptation and convergence through multi-omic analyses, including analyses of host genomes and transcriptomes, as well as gut metagenomes, in combination with validating assays of key enzymes’ activities, in the species of three mammalian order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 91 publications
3
16
0
1
Order By: Relevance
“…More specifically, CHIA5 was found expressed at particularly high levels in the stomach and salivary glands. These results are in line with previous proteomic studies that have also identified CHIA5 as a digestive enzyme (Zhang et al 2019), which has been confirmed to be highly expressed by RT-qPCR in the specialized oxyntic glands stomach (Ma et al 2018a;Cheng et al 2022), reflecting a key adaptation of the Malayan pangolin to its strictly myrmecophagous diet. By contrast, in the southern tamandua (T. tetradactyla) only CHIA5 is pseudogenized (Emerling et al 2018;Cheng et al 2022).…”
supporting
confidence: 91%
See 4 more Smart Citations
“…More specifically, CHIA5 was found expressed at particularly high levels in the stomach and salivary glands. These results are in line with previous proteomic studies that have also identified CHIA5 as a digestive enzyme (Zhang et al 2019), which has been confirmed to be highly expressed by RT-qPCR in the specialized oxyntic glands stomach (Ma et al 2018a;Cheng et al 2022), reflecting a key adaptation of the Malayan pangolin to its strictly myrmecophagous diet. By contrast, in the southern tamandua (T. tetradactyla) only CHIA5 is pseudogenized (Emerling et al 2018;Cheng et al 2022).…”
supporting
confidence: 91%
“…These results are in line with previous proteomic studies that have also identified CHIA5 as a digestive enzyme (Zhang et al 2019), which has been confirmed to be highly expressed by RT-qPCR in the specialized oxyntic glands stomach (Ma et al 2018a;Cheng et al 2022), reflecting a key adaptation of the Malayan pangolin to its strictly myrmecophagous diet. By contrast, in the southern tamandua (T. tetradactyla) only CHIA5 is pseudogenized (Emerling et al 2018;Cheng et al 2022). Although CHIA1 and CHIA2 are functional, they did not appear to be expressed in the organs of the digestive tract of the southern tamandua individual sampled here (Fig.…”
supporting
confidence: 91%
See 3 more Smart Citations